Kedudukan Wanita dalam Perspektif Syi’ah - Harisman Harisman (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2015)
Women have a respectable position in Islam. Besides already mentioned in some verses of the Qur’an, the virtue of women is also much expressed through the words of the Prophet SAW. However, it will be different when viewed from the Shites perspective. the sect, that claimed that the entire thought derived from the Ahl al-Bayt turned out to have a different view with regard to the position of women. The discussion in this paper is more emphasis on the study of Turath. Turath study is intended study of classic books written by scholars of shi’ah. The research focused on women’s rights in various aspects. The conclusion that can be drawn from this paper turns Shites tend to demean women. From the side of the faith, Shite women will certainly not obtain a higher degree of faith than men. Starts from this, they deny some rights that should be owned by women. Rights are neglected, among others: the right to religious education and the public, rights in muamalah (relationship), and the right in the household. Especially, when women are faced with a belief in the urgency of Mut’ah, then by itself be marginalized women. Due to Mut’ah are supported by the shariah, actually is a form of insult the dignity of women.